THE ROLE OF MONETARY AND FISCAL POLICY IN THE DEVELOPMENTAL FINANCING OF THE ECONOMY IRAQI AFTER 2003 (World Economics and Finance Bulletin, 2022)
At a time when most of the developing countries during the seventies tended towards borrowing and indebtedness from official and private sources and used those funds in the field of investment and consumer spending and the aggravation of their indebtedness as a result of the misuse of those funds, Iraq was going through during that period a stage of economic recovery because of oil, and that stage achieved It has large financial surpluses, so that the Iraqi economy became the second strongest Arab economy during the seventies after Saudi Arabia, and its annual revenues were estimated at 9 billion dollars, and the average per capita GDP was approximately 2900 dollars, and the foreign assets of the Central Bank were estimated at 36 billion dollars, excluding gold. Oil prices during 1973-1979. With large financial surpluses estimated at $93 billion.This does not mean that Iraq was not indebted during the seventies, but the value of the debt was small compared to it being one of the oil-producing Arab countries that provided loans and aid to the Arab and non-oil developing countries.
Keywords: monetary and monetary policy, development financing